Avaliação do efeito do disseleneto de difenila em modelo de doença de Alzheimer no nematódeo Caernorhabditis elegans - Zamberlan, Daniele Coradini (2014)
Alzheimer s (DA) is a neurodegenerative disease evidenced by cognitive disorders and attention deficit and learning, and is the main cause of dementia in the elderly. The amyloid hypothesis posits that extracellular amyloid-β (Aβ) deposits are the fundamental etiological factor of the disease. However, the AD etiology has yet to be fully understood and common treatments remain largely non-efficacious. Caernorhabditis elegans transgenic strains expressing toxic Aβ has been employed as AD in vivo model in order to elucidate mechanisms and verifying the effectiveness of pharmacological compounds. The organoselenium compound tested in this study, Diphenyl-diselenide (PhSe)2, has shown efficacy in ameliorate several parametres in neurodegenerative disease models. In the present study, we analyzed the effects of (PhSe)2 chronic treatment on Aβ peptide-induced toxicity in C. elegans. This data shows that chronic exposure to (PhSe)2 attenuated oxidative stress induced by Aβ with concomitant recovery of associative learning memory in worms. In addition, (PhSe)2 decreased Aβ transgene expression, suppressing the Aβ peptide and down-regulating hsp-16.2 by reducing the need of this chaperone under Aβ toxicity. This observations suggest that (PhSe)2 plays an important role in protection against oxidative stress-induced toxicity, this representing a promising potential pharmaceutical modality by attenuating Aβ expression.